Effectiveness of silica fume lightweight foam concrete wall panel with window opening under axial load - Sulaiman, Mat Rani (2010)
Structural wall with opening are widely used as lateral load bearing elements in designing earthquakes resistant for building. Therefore, this study was investigated the performance of lightweight foam concrete with window opening under axial load. The Reinforced Lightweight Foam Concrete with 15% of Silica Fume (SFRLWC) behavior was analyzed and discussed in term of ultimate load, maximum deflection and mode of failure compare to conventional concrete. The cube test (compressive strength test) showed that the SFRWC-WPWO was 46% higher than conventional concrete but the weight was 22% lower than the conventional concrete. In this study, the ultimate load of SFRWC-WPWO was 34% higher than conventional concrete with magnitude of 482kN. The deflection of SFRWC-WPWO was 41% lower than conventional concrete with magnitude of 5.57mm. The failure mode for conventional concrete is due to cracking and SFRWC-WPWO was not failed under 500kN axial load test. Finally, the study explained that the lightweight foam concrete were fragile but more effective compared to conventional concrete in term of compressive strength of cube test, axial load test and the cracking and mode of failure.